1994
DOI: 10.1111/j.1752-1688.1994.tb03291.x
|View full text |Cite
|
Sign up to set email alerts
|

POTENTIAL EFFECTS OF DEVELOPMENT ON FLOW CHARACTERISTICS OF TWO NEW JERSEY STREAMS1

Abstract: Parts of the Raritan River basin in central New Jersey have undergone increasing development over the last several decades. The increasing population relies on the region's ground water and surface water sources for its residential, commercial, and industrial water supply. Urbanization, regionalized wastewatertreatment facilities, stream channel alterations, and interbasin transfers of water can all affect water availability. This pilot study was conducted to determine whether significant trends exist in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 4 publications
0
22
0
1
Order By: Relevance
“…Streams with moderate %TIA had the highest levels of discharge and highest rates of litter breakdown. Unlike streams in other urbanized areas elsewhere in North America (), it appears that urbanization in the lower St. Johns catchment may result in an increase in base flow (Klein 1979, Barringer et al 1994). In our experience, small streams in Northeast Florida with natural land‐cover are intermittent, while similar‐sized streams in urbanized areas are perennial.…”
Section: Discussionmentioning
confidence: 99%
“…Streams with moderate %TIA had the highest levels of discharge and highest rates of litter breakdown. Unlike streams in other urbanized areas elsewhere in North America (), it appears that urbanization in the lower St. Johns catchment may result in an increase in base flow (Klein 1979, Barringer et al 1994). In our experience, small streams in Northeast Florida with natural land‐cover are intermittent, while similar‐sized streams in urbanized areas are perennial.…”
Section: Discussionmentioning
confidence: 99%
“…Their model projected a 2% decrease, and a 7% increase in annual streamflow for the CCC and Hadley predictions, respectively. Urbanization has been observed to lead to enhanced peak flows and reduced base flows by Leopold (1968), Klein (1979), Barringer et al (1994), and Paul and Meyer (2001). Paul and Meyer (2001) also found that urbanizing watersheds exhibit a larger volume of the received precipitation as surface runoff and less as groundwater flow.…”
Section: Introductionmentioning
confidence: 92%
“…Other studies have observed increases in groundwater recharge or base flow with urbanization that is credited to water supply pipe leakage [ Lerner , ], reduced evapotranspiration, focused recharge of storm water infiltration [ Ku et al ., ; Appleyard , ; Stephens et al ., ; Hogan et al ., ], recovery from industrial groundwater pumping [ Vázquez‐Suñé et al ., ], or discharge of wastewater from imported or confined water supply [ Burns et al ., ; Townsend‐Small et al ., ]. Where a range of these features was present and the increases and decreases nearly balanced out, or the effects on urban development were small compared to predevelopment recharge, little effect was observed from urban development on groundwater recharge or base flow [ Ferguson and Suckling , ; Barringer et al ., ; Yang et al ., ; Kim et al ., ; Trowsdale and Lerner , ; Brandes et al ., ; Meyer , ; Roy et al ., ]. The effect of any given city on groundwater levels will likely vary over time as the city develops [ Kennedy et al ., ].…”
Section: Introductionmentioning
confidence: 99%